2010
DOI: 10.3892/ijo_00000781
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological inhibition of Rho-kinase (ROCK) signaling enhances cisplatin resistance in neuroblastoma cells

Abstract: Abstract. The role of the RhoA/Rho kinase (ROCK) signaling pathway in cell survival remains a very controversial issue, with its activation being pro-apoptotic in many cell types and anti-apoptotic in others. To test if ROCK inhibition contributes to tumor cell survival or death following chemotherapy, we treated cisplatin damaged neuroblastoma cells with a pharmacological ROCK inhibitor (Y27632) or sham, and monitored cell survival, accumulation of a chemoresistant phenotype, and in vivo tumor formation. Addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…In the present study MTX prominently induced histopathological changes and hepatic tissue injury as found by histopathological examination. This was in agreement with preceding studies [8], which found that MTX can induce hepatic lesions, such as focal fibrosis, congestion, and dilatation of sinusoids with fatty vacuolation, and portal vein inflammation [31], which could be recognized, as the liver is the major site of MTX metabolism into the toxic agent 7-hydroxy-MTX, and the MTX can be stored inside hepatocytes in polyglutamated form, leading to hepatotoxicity [32,33].…”
Section: Discussionsupporting
confidence: 92%
“…In the present study MTX prominently induced histopathological changes and hepatic tissue injury as found by histopathological examination. This was in agreement with preceding studies [8], which found that MTX can induce hepatic lesions, such as focal fibrosis, congestion, and dilatation of sinusoids with fatty vacuolation, and portal vein inflammation [31], which could be recognized, as the liver is the major site of MTX metabolism into the toxic agent 7-hydroxy-MTX, and the MTX can be stored inside hepatocytes in polyglutamated form, leading to hepatotoxicity [32,33].…”
Section: Discussionsupporting
confidence: 92%
“…Our preliminary experiments on the effect of blebbistatin on apoptotic cells did show inhibition of water loss, but much more extensive studies would be needed for definitive conclusions. The problem with blebbistatin is that it inhibits apoptosis in general (Xiao et al, 2009;Street et al, 2010;Li et al, 2018;Chai et al, 2019). While such inhibition is compatible with the view that (1) cytoskeletal compression causes dehydration and that (2) dehydration is needed for apoptosis, one cannot claim that blebbistatin inhibits AVD if apoptosis is no longer present.…”
Section: Intracellular Pressurementioning
confidence: 99%
“…Treatment with ROCK inhibitor Y27632 led to increased migration and mitotic activity in breast, colon and pancreatic cancer cell cultures (12)(13)(14)(15). Others showed that inactivation of ROCK signaling promoted cell survival and attenuated drug-induced apoptosis in leukemia, neuroblastoma and ovarian carcinoma (16)(17)(18), as well as increased cancer cell stemness (19,20). These seemingly contradictory findings may be at least partly attributed to the choice of different cell lines in various studies.…”
mentioning
confidence: 99%